2009
DOI: 10.1002/ibd.20923
|View full text |Cite
|
Sign up to set email alerts
|

Il-21 enhances NK cell activation and cytolytic activity and induces Th17 cell differentiation in inflammatory bowel disease

Abstract: IL-21 enhances IBD NK cell cytotoxic response, triggers T cells to produce proinflammatory cytokines, and induces IBD CD4(+) T cells to differentiate into Th17 cells, suggesting that IL-21 is involved in the pathogenesis of IBD and that blocking IL-21R signaling may have a therapeutic potential in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 43 publications
2
59
2
3
Order By: Relevance
“…Our recent work has also demonstrated that IL-21R-positive cells were increased significantly in the inflamed mucosa of IBD patients. Importantly, IL-21 could enhance the IBD NK cell cytotoxic response, trigger IBD T cells to produce proinflammatory cytokines and induce IBD CD4 + T cells to differentiate into Th17 cells [15]. These data indicate that IL-21 plays an important role in the pathogenesis of IBD, and neutralizing IL-21 may have a therapeutic potential in the management of IBD.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our recent work has also demonstrated that IL-21R-positive cells were increased significantly in the inflamed mucosa of IBD patients. Importantly, IL-21 could enhance the IBD NK cell cytotoxic response, trigger IBD T cells to produce proinflammatory cytokines and induce IBD CD4 + T cells to differentiate into Th17 cells [15]. These data indicate that IL-21 plays an important role in the pathogenesis of IBD, and neutralizing IL-21 may have a therapeutic potential in the management of IBD.…”
Section: Introductionmentioning
confidence: 85%
“…All PCR reactions were run in triplicate and performed with 40 cycles using the following conditions: 95°C for 1 min, followed by 40 cycles at 95°C for 15 s and 60°C for 30 s. The relative target gene expression levels were calculated as a ratio relative to the b-actin reference mRNA. Quantitative real-time PCR analysis was carried out using the 2-᭝᭝Ct method [15,23,24].…”
Section: Quantitative Real-time Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation indicated that IL-21 is capable of inducing NK-cell activation in patients with ESCC. Furthermore, the observation for upregulated IL-21R was also found in NK cells of patients with inflammatory bowel disease (IBD) (Liu et al, 2009), suggesting that the expression of IL-21R on NK cells may be upregulated in response to chronic inflammatory reactions such as IBD or ESCC. The response to IL-21 is also affected by a polymorphism in the IL-21R gene (Pène et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Care was taken to make sure that the patients matched the diagnostic criterias and didn't suffer from chronic diseases such as chronic viral infections (Elsaesser et al, 2009), SLE (Sarra et al, 2010), Rheumatoid Arthritis (Daha et al, 2009), Psoriasis (Liu et al, 2008) and Inflammatory bowel diseases (Liu et al, 2009). Written consent was obtained from all the patients concerned in order to perform this study.…”
Section: Methodsmentioning
confidence: 99%